PENGEMBANGAN SISTEM OTOMATISASI PENGENDALI ALAT PENDINGIN BERDASARKAN SUHU RUANGAN DENGAN MENGGUNAKAN SENSOR LM35 - I Gede Ketut Ari Wirawan; I Made Anggi Wahyudi Artha; Rukmi Sari Hartati; Ida Bagus Gede Manuaba (Program Studi Teknik Elektro UNUD, 2025)
Indoor temperature and humidity control plays an important role in creating a comfortable and energy-efficient environment, especially in tropical areas such as Denpasar, Bali. Manual use of air conditioners (AC) is often less than optimal because it does not consider the actual environmental conditions as a whole. This study designs an AC control automation system based on the Internet of Things (IoT) concept that can be controlled via a web interface. This system combines several sensors, such as LM35 for temperature, DHT22 for humidity, and PIR for motion detection, and is controlled by an Arduino UNO microcontroller. In addition, data transmission is carried out via the HM-10 Bluetooth module and a web-based monitoring interface built using the Python programming language. The developed system is able to display temperature, humidity, and user presence data in real time, and automatically regulates AC operation based on these environmental conditions. Tests show that the LM35 sensor has an error of 1,42% and the DHT22 sensor is 0.73%, with an effective range of PIR and IR sensors of up to 4 meters. Overall, this system has succeeded in saving AC energy consumption by up to 35.49%. Based on these results, this system is considered feasible to be applied in real environments as an efficient and adaptive temperature control solution.